Lifestyle Interventions to Improve Pregnancy Outcomes: a Systematic Review and Specified Meta-Analyses - Behnam, Susann; Timmesfeld, Nina; Arabin, Birgit (Geburtshilfe und Frauenheilkunde, 2022)
To compare the impact of lifestyle interventions for overweight and obese pregnant women a systematic review and meta-analysis was conducted using pre-registration and audit of the interventions as selection criteria.PubMed, Web of Science and CENTRAL were searched for randomized controlled trials examining diet, exercise, combined interventions or associated behavioral therapy. Trials were selected if they reported one of the primary outcomes (gestational diabetes, hypertensive disorders, perinatal mortality, admission to neonatal intensive care unit). Results were established from the total group and separately from pre-registered or clinically audited studies.Out of 1304 titles, 28 randomized controlled trials were included. Among the primary outcomes only hypertensive disorders were significantly reduced by exercise in the total group: odds ratio 0.52 (95% confidence interval 0.28 to 0.96, four trials, 1324 participants). When behavioral therapy supported combined interventions, maternal weight gain, (Standardized Mean Difference −0.16 kilogram; 95% confidence interval −0.28 to −0.04, four trials, 2132 participants) and neonatal birthweight, (Standardized Mean Difference −0.4 gram; 95% confidence interval −0.62 to −0.18, five trials, 1058 participants), were significantly reduced within the total group and both specified meta-analyses. Higher frequencies of physical activity improved the results. Risk of bias, assessed with the Cochrane Tool, was low to moderate.Elements of behavioral therapy might better prevent adverse effects of maternal obesity when combined with lifestyle interventions. Unfortunately, high heterogeneity due to different intervention and population characteristics was a limiting factor. Future studies should also focus on increased intensities of physical activity.
Keywords: Übergewicht; HELLP-Syndrom; Präeklampsie; Diabetes mellitus; körperliche Betätigung; Ernährung